Fresno State vs. San Jose State Evening Football Game at Bulldog Stadium - Watkins, Howard::::::::: (1989)
Robin Watkins, Frances Kamp, Adam Watkins wearing Fresno State sweatshirt with gray bulldog head mask and Howard Watkins in stands